Ṣūfī and Sultāns in Southeast Asia and Kurdistan: A Comparative Survey - Bruinessen, Martin van (Studia Islamika, 1996)
This paper describes the stories about the relationship between Sufi with the king in the process of Islamization of a society that is a lot of coloring the literature in the Muslim world. This happens due to the fact that the relationship between the world religions (spiritual) with the world powers (the material) is always a problem that is somewhat typical. On the one hand, people tend to assume that a Sufi should not approach politics, because it is contrary to the ascetic world she lived.DOI: 10.15408/sdi.v3i3.798